2002
DOI: 10.1067/mge.2002.127101
|View full text |Cite
|
Sign up to set email alerts
|

Minute findings by magnifying colonoscopy are useful for the evaluation of ulcerative colitis

Abstract: Our proposed classification of magnifying colonoscopic findings in patients with ulcerative colitis is useful for the evaluation of disease activity and for the prediction of periods of remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…[4][5][6] Other studies have reported the features of magnifying colonoscopy to be associated with the histological activity of UC and the prediction of disease relapse. 7,8 In the present study we investigated whether relapse of disease within 12 months could be predicted by precise observation of the surface colonic mucosa, especially by the findings of small defects, fine network, and crypt opening pattern on the surface epithelial mucosa by magnifying colonoscopy in patients with quiescent UC. Moreover, we compared the relationship between magnifying colonoscopic and histological findings.…”
mentioning
confidence: 99%
“…[4][5][6] Other studies have reported the features of magnifying colonoscopy to be associated with the histological activity of UC and the prediction of disease relapse. 7,8 In the present study we investigated whether relapse of disease within 12 months could be predicted by precise observation of the surface colonic mucosa, especially by the findings of small defects, fine network, and crypt opening pattern on the surface epithelial mucosa by magnifying colonoscopy in patients with quiescent UC. Moreover, we compared the relationship between magnifying colonoscopic and histological findings.…”
mentioning
confidence: 99%
“…In particular, the correlation between histopathologic grade and magnifying colonoscopic findings (r 2 = 0.807) was better than that for histopathologic grade versus conventional colonoscopy (r 2 = 0.665). This study found that patients in whom MDE was observed during clinical remission frequently experienced relapse within short periods (6 mo) compared with those without this finding, and that 50% of patients who underwent clinical remission still had active inflamed mucosa with MDE [15] . This latter finding correlates with a previous finding that 30% to 60% of patients in remission as determined by clinical symptoms were still in the active stage of ulcerative colitis based on histopathologic findings [18,31] .…”
Section: Evaluation Of Ulcerative Colitismentioning
confidence: 66%
“…Further, the presence of breaches in surface epithelium may be an additional factor in future relapse [3] , and an altered pattern as defined by magnified colonoscopic views may be predictive of course [14] . Fujiya et al [15] proposed a classification system for magnifying colonoscopic findings in patients with UC which has proved useful for the evaluation of disease activity and prediction of periods of remission. This classification references regularly arranged crypt openings, a villous-like appearance, minute defects of epithelium (MDE), small yellowish spots (SYS), and a coral reeflike appearance.…”
Section: Evaluation Of Ulcerative Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore it has been suggested that the presence of branches in surface epithelium may be a factor that predicts future disease relapse [15] , and they suggested that altered pattern as defined by magnified colonoscopic views may be predictive of the course of ulcerative colitis [65] . Fujiya et al proposed the classification of magnifying colonoscopic findings in patients with ulcerative colitis which is useful for the evaluation of disease activity and for the prediction of periods of remission [66] . The classification was devised as follows: regularly arranged crypt opening, villous-like appearance, minute defects of epithelium (MDE), small yellowish spots (YS), and coral reef-like appearance.…”
Section: Prediction Of Relapse In Patients With Quiescent Ulcerative mentioning
confidence: 99%